Investigating the level of alignment between the municipal capital budgets and the spatial development frameworks in the Ehlanzeni district municipality - Pulumo, Nwabisa (Stellenbosch : Stellenbosch University, 2015)
Thesis (MA)--Stellenbosch University, 2015.